THE IMPACT OF COVID-19 ON THE EXPORT–ECONOMIC GROWTH RELATIONSHIP IN INDONESIA, 2019-2020 - Pratomo, Yulius (Jurnal Studi Ekonomi dan Pembangunan, 2025)
This study examines the moderating effect of the Covid-19 pandemic on the relationship between exports and economic growth in Indonesia. Specifically, it analyzes whether variations in additional Covid-19 cases across provinces weaken the impact of changes in the share of real exports on provincial real Gross Regional Domestic Product (GRDP) growth. The analysis applies a dynamic panel data approach using the Generalized Method of Moments (GMM) to address potential endogeneity. The study uses quarterly provincial-level panel data for Indonesia (34 provinces) over the period 2019–2020, with a total of 136 observations. The findings reveal that the Covid-19 pandemic significantly weakens the positive effect of exports on economic growth, although the moderating effect is relatively small than both the direct effect of exports and the direct negative impact of the pandemic. These results suggest that pandemic containment policies should be designed in balance with economic recovery strategies and underscore the importance of considering non-economic shocks in supply-side macroeconomic analysis.Keywords: COVID-19 Pandemic; Economic Growth; Exports; Panel Data Analysis